2007
DOI: 10.1007/s10903-006-9035-5
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence in Indians from Three Areas: Delhi and Mumbai, India, and British Columbia, Canada

Abstract: Cancer incidence patterns in BC Indo-Canadian men and women differed from those in India, being more similar to the BC general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The limitations of this proxy have been discussed elsewhere, 4 5 including that, especially in European countries with colonial histories such as Scotland, many of the elderly were born abroad, and substantial proportions (often 50% or more) of resident ethnic minority populations are not born abroad. Name search methods are also popular [6][7][8][9] but have even more limitations, for example, they are not good for studying White minority groups and African and Caribbean origin Black populations. 4 5 A recent survey of European cancer registries concluded that while self-reported ethnicity was the exemplary variable, none of 79 registries analysed data this way, with Scotland being closest to achieving this goal.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations of this proxy have been discussed elsewhere, 4 5 including that, especially in European countries with colonial histories such as Scotland, many of the elderly were born abroad, and substantial proportions (often 50% or more) of resident ethnic minority populations are not born abroad. Name search methods are also popular [6][7][8][9] but have even more limitations, for example, they are not good for studying White minority groups and African and Caribbean origin Black populations. 4 5 A recent survey of European cancer registries concluded that while self-reported ethnicity was the exemplary variable, none of 79 registries analysed data this way, with Scotland being closest to achieving this goal.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…[12][13][14][15] Most available studies in Europe analyse data at a point or period of time, that is, cross-sectional analyses using numerators and denominators from different sources, creating potential errors in calculations of rates. 3 16 The field is developing internationally with recent work using name search methods in Canada 6 and linkage methods in New Zealand, 17 with interest in multination comparisons for specific ethnic groups. 18 Ethnic variations in cancer, mostly using country of birth, 3 have been noted with, for example, comparatively lower mortality for all combined and four major cancers in South Asian migrants in England and Wales.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…and time since immigration so that, depending upon the cancer site and relative risk within country of origin, cancer risk may increase to approach risk similar to that of the host country, [19][20][21][22][23] or alternatively, decrease for some cancer sites in comparison to that within the host country. 22,23 As the composition of Canada continues to change, 1 challenges to providing comparable information regarding patterns of cancer risk among immigrants at both the national and subnational level persist.…”
mentioning
confidence: 99%
“…[11] The cancer incidence among migrated population, BritishColumbia, Indio-Canadian men women differ from the Indian population. [12] If the vital registration system is complete and it covers to a great extent only then can one rely on the registration system. But till now there is no satisfactory level of registration.…”
Section: Discussionmentioning
confidence: 99%